Towards Sustainable Development Goals: Indexing the performance of Bangladesh in achieving the MDGs - Zaman, Nabila (BRAC Institute of Governance and Development (BIGD), 2022)
The study evaluated the performance of regions in Bangladesh, both across divisions and districts, in their attainment of Millennium Development Goals (MDGs). Based on the data from the Multiple Cluster Survey and applying the formulated Mazziotta Pareto Index (MPI), the findings show that there remain contradictory results across divisions and districts. Although Bangladesh is performing well at the national level for its attainment of MDG goals, at the more micro level, the analysis suggests that Bangladesh is yet to outperform in achieving all health and education social developments. Thus, the paper makes a policy suggestion for the policy-makers, academicians and development practitioners to identify these governance gaps for better achievements of the Sustainable Development Goals.